Determining Per Capita Value of Urban Green Spaces Provision: A Case of Eldoret Town, Kenya - B.A, Goro; B.N, Mwasi (Africa Environmental Review Journal, 2017)
Urban green spaces (UGS) form an important component of the urban environment. They provide a range of environmental, health, and social services that improve the quality of life in cities. The World health Organization recommends a minimum standard of 9m2 of green space per capita in a sustainable City. Unfortunately, green spaces are not being provided to match the growing urban population. This study analyzed green spaces in Eldoret Central Business District (CBD) and its environs against its urban core population to determine whether the per capita green space available makes significant contribution to its urban life. The research used remote sensing data from Google earth taken in July 2014 and Spatial Analysis tool in ArcGIS 10.1. The results reveal that the available green spaces cover 465,567m2, an area equivalent to 26% of the total study area, and a per capita value of 2.5m2. The available green spaces therefore, do not make significant contribution to urban life due to its low per capita availability. They fall below the WHO recommended standard of 9 m 2 per capita, indicating a shortage of 6.5m 2 per capita green space- an equivalent of approximately 1,676,041 square meters of green space. As a result, urban planning should focus more on expansion of green spaces especially within the Central Business District towards a sustainable town.